DNA CLONING AND MOLECULAR CHARACTERIZATION OF H2A AND H4 GENES IN PEPPER - Ming-Hua Deng; Hui Zhou; Jin-Long Huo; Jun-Heng Lv; Jin-Fen Wen; Hai-Shan Zhu (Journal of Animal and Plant Sciences, 2015)
The complete coding sequences (CDS) of “Yunnan Purple Pepper No.1” (Capsicum annuum L.) H2A and H4 genes were amplified using the reverse transcriptase polymerase chain reaction based on the conserved sequence information of some Solanaceae plants and known highly homologous pepper ESTs. The nucleotide sequences analysis of these two genes revealed that pepper H2A gene encodes a protein of 142 amino acids that has high homology with the H2A-like protein of 5 species: matrimony vine, grape, alfalfa, arabidopsis and maize. Sequence analysis of the second gene revealed that the pepper H4 encodes a protein of 103 amino acids that has high homology with the proteins of 4 species: tomato, tobacco, eggplant and petunia. The tissue expression analysis indicated that the pepper H2A and H4 genes were moderately expressed in the seven tissues. Our experiment established the primary foundation for further research on these two pepper genes.
Keywords: Capsicum annuum L.; H2A; H4; Gene expression profile; Bioinformatics analysis